Application value of EV/EV71/CA16-SAT detection in children with hand-foot-mouth disease: Detection in children with hand-foot-mouth disease - Cai, Jingjuan; Lv, Hai; Ding, Xianping; Zhao, Yun; Yu, Chunli; Luo, Yan; Wang, Zijing; He, Lu; Sun, Zhaohua; Lu, Yaling; Yang, Lifu; Chen, Fei; et al. (Cellular and Molecular Biology, 2023)
The objective of this work was to explore the application value of a new type of fluorescent nucleic acid isothermal amplification (SAT) to detect EV/EV71/CA16-SAT in children with hand-foot-mouth disease (HFMD). For this purpose, from March 2017 to September 2019, Chengdu Children’s Specialized Hospital collected throat swabs from children with clinical manifestations of hand, foot and mouth disease, and used SAT technology to screen and detect universal enterovirus (EV) nucleic acid (There were 1860 children with EV-RNA) positive. Patients who are EV-RNA positive at any time: first use the same throat swab specimen to detect EV71/CA16-RNA; secondly, collect venous blood and use the colloidal gold method to detect IgM antibodies in EV71/CA16 serum. The patients with positive EV71/CA16-RNA or EV71/CA16-IgM (or both) were repeated the above two methods 2 weeks and 4 weeks after standard treatment for review and comprehensive analysis. Results showed that 763 cases were enrolled for the first time: 59.76% were male and 40.24% were female; the age ranged from 1 month to 13 years, of which 69.06% were from 1 to 4 years old; CA16-RNA positive 56.23%, EV71-RNA positive 21.89%, CA16/EV71 -RNA were all positive in 1.57%; CA16-IgM was positive in 64.48%, EV71-IgM was positive in 54.26%, and CA16/EV71-IgM were both positive in 18.74%. After 2 weeks, 722 cases were reexamined: 26.73% were positive for CA16-RNA, 7.89% were positive for EV71-RNA, 0.28% were both positive for CA16/EV71-RNA; 66.21% were positive for CA16-IgM, 51.52% were positive for EV71-IgM, and IgM were all positive in 17.73%. Four weeks later, 489 cases were reexamined: among them, CA16-RNA positive 5.73% of which were positive for EV71 color RNA (0.005%), and 12.68% of them were all positive for EV71lym. The strategy of combining SAT technology and colloidal gold method to detect EV/EV71/CA16 nucleic acid (RNA) and serum IgM antibody in children HFMD can improve the early detection rate and accuracy of HFMD; According to the comprehensive analysis of the detection results of children with HFMD at the early stage, 2 weeks and 4 weeks of the present study, it is suggested that EV/EV71/CA16-SAT nucleic acid detection can be used to judge the prognosis, follow-up treatment, set isolation time, return students to school, and community management in children with HFMD. and prevention and control have more clinical application value.